PENGEMBANGAN INDUSTRI KLASTER JAMBU METE DI JAWA TIMUR - Bedy Sudjarmoko; Agus Wahyudi (Jurnal Tanaman Industri dan Penyegar, 2011)
Industrial cluster approach as an development strategy has been adopted nationally and continues to be strengthened in recent years. National Development Programme of 2003 mandated the cluster approach in the development of small and medium industries. Presidential Regulation No. 07 of 2005 states that national industrial development focused on strengthening and growth of the ten priority industrial clusters. The research is aimed to formulated strategy of cashew ind ustry cluster development in East Java. The data used are primary and secondary data, analyzed using Porter's Diamond. The research was conducted in S umenep, Sampang, and Bangkalan, using the survey in March - April 2011. Data analysis was conducted descriptively using Porter's Diamond Model. The results showed that the cashew industry cluster in East Java has not been going well as expected. The linkage between upstream and downstream industries are still weak, so is the quality of the products produced. Classical problems which have obstructed the development of the cashew industry in this region are crop productivity, product quality, regulatory and policy difficult to implement, still can not fully overcome. Determinant factor is the key to successful development of industrial clusters is the availability of raw cashew nuts, infrastructure, government policy, the interaction between players in the industry, the availability of supporting institutions, upstream and downstream industries, product demand conditions and the availability of foreign investors. Therefore, the handling can not be done spatially, must be supported by all sides and done in an integrated way. Cashew cluster industry development strategy needs to be done by improving government policy (regulation of markets for industrial products cashew, cashew export tax implementation, mandatory SNI nut products, improvement of the domestic market); strengthening the upstream and downstream industries (productivity and quality of cashew, increase the ability of the cashew processing industry); and optimization of the interaction between the core industry by supporting industry and other related institutions (farmers' cashew, cashew industry, food industry and beverage, industrial equipment & machinery, exporters, traders, government agencies, research and development institutes, associations industry, transportation and financial services/banking).